Trouble in paradise? or Ethical Dilemmas in the Accounting Management of A Religious Organization, A Case Study - Chávez-Díaz, Jorge Miguel (2024)
This case study explores the ethical dilemmas faced by the accounting staff of a religious organization. The object of study is an important religious organization in Peru with national scope and affiliation abroad. The method is qualitative, and the ethical pattern is analyzed through the Nagel-Baud model to identify the reason or motivation of the decisions. Twelve ethical dilemmas faced by the accounting personnel in the organization are obtained. Likewise, it is established that the values of the religious organization are prioritized over the accounting ethics contained in the Peruvian Code of Ethics. Justification is obtained from the point of view of dogma and religious practice by the accounting staff. The research concludes that professional accounting ethics should be emphasized in the conduct of the professional before religious values and recommends that the accounting personnel should be external as well as the obligatory nature of the internal control area.